CPSF6 defines a conserved capsid interface that modulates HIV-1 replication. - Amanda J Price; Adam J Fletcher; Torsten Schaller; Tom Elliott; KyeongEun Lee; Vineet N KewalRamani; Jason W Chin; Greg J Towers; Leo C James (PLoS Pathogens)
The HIV-1 genome enters cells inside a shell comprised of capsid (CA) protein. Variation in CA sequence alters HIV-1 infectivity and escape from host restriction factors. However, apart from the Cyclophilin A-binding loop, CA has no known interfaces with which to interact with cellular cofactors. Here we describe a novel protein-protein interface in the N-terminal domain of HIV-1 CA, determined by X-ray crystallography, which mediates both viral restriction and host cofactor dependence. The interface is highly conserved across lentiviruses and is accessible in the context of a hexameric lattice. Mutation of the interface prevents binding to and restriction by CPSF6-358, a truncated cytosolic form of the RNA processing factor, cleavage and polyadenylation specific factor 6 (CPSF6). Furthermore, mutations that prevent CPSF6 binding also relieve dependence on nuclear entry cofactors TNPO3 and RanBP2. These results suggest that the HIV-1 capsid mediates direct host cofactor interactions to facilitate viral infection.